The Implementation of Blended Learning in Akidah Akhlak Lesson during Covid-19 Pandemic in Madrasah - Tambunan, Qurrota A'yuna; Sinaga, Ali Imran; Salamuddin, Salamuddin (Universitas Pahlawan Tuanku Tambusai, 2022)
Aqidah Akhlak is one of the branches of Islamic Religious Education which is expected in its learning to give meaning either directly or indirectly. Blended Learning is a learning that is an alternative in managing time effectively in addition to conventional techniques that are implemented for Aqidah Akhlak subjects in madrasas. This study aims to describe and analyze the implementation of Blended Learning Aqidah Morals during the Covid-19 period in madrasas. This research uses qualitative research methods with the type of field research research through a descriptive approach. Data was collected using interview, observation and document analysis techniques. Furthermore, the data were analyzed through data reduction (sorting) techniques, data presentation and drawing conclusions. The results of this study indicate that the implementation of Aqidah Akhlak Blended Learning during the Covid-19 period in madrasas has been properly and appropriately implemented, this is evidenced by the existence of planning by designing learning program objectives, preparing facilities and infrastructure, preparing schedules and socialization, then implementing learning a combination of online and face-to-face, as well as evaluations in the form of examinations and collection of daily assignments, Mid-Semester Exams (UTS), and Final Semester Exams (UAS) at madrasas.